ANALYSIS OF RAW MATERIAL INVENTORY CONTROL USING THE ECONOMIC ORDER QUANTITY (EOQ) METHOD, SAFETY STOCK (SS), AND REORDER POINT (ROP) ON THE PRODUCTION OF FOOTWEAR HARIS JAYA WEDORO SIDOARJO METHODS - Melinda Mega Puspita; Reswanda Reswanda (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2020)
Haris Jaya Footwear Production is a business that produces sponge slippers located in the Sidoarjo region. In conducting its production activities it is closely related to the supply of raw materials which are important components that must be available for the smooth production process. The purpose of this study is to find out how to stock the raw material of footwear with the EOQ method efficiently, Know the optimal amount of safety stock, and be able to determine the point of re-ordering raw materials (ROP) so that the production process is not obstructed. The method used in this study is descriptive qualitative. The results showed that by applying the EOQ method, (1) the total cost of raw material inventory for Haris Jaya Footwear Production when calculated using the EOQ method was IDR 30,342,940, while the Haris Jaya Footwear Production policy was IDR 37,363,478. Cost savings when using the EOQ method is Rp 7,020,538 or can reduce costs by up to 18%. (2) The optimal amount of raw material for Eva sponges is 22 sheets. (3) And reorder when the Eva sponge raw material in the warehouse reaches 45 sheets.